Evaluation Of Electronic Medical Record Data Security Based On Basic Aspects Of Information Security - Dian Felinda; Ahmad Amiruddin; Niska Salsiani Sinta (International Journal of Multidisciplinary Learners, 2025)
Within the angle of overseeing electronic wellbeing information data security, it could be a combination of mechanical and organizational viewpoints. The strategy chosen for this will moreover have an affect on the taken a toll, complexity and level of security delivered. The innovative perspective can be utilized to control confirmation, authorization, keenness, review trails, post-disaster recuperation, secure information capacity and transmission.. This research aims to find out how to evaluate the security of electronic medical record data in dealing with cybersecurity threats at BLUD RSUD Baubau City in 2024. This research was conducted at BLUD RSUD Baubau City Year 2024. The method used is using a descriptive type of approach with a qualitative approach and the method of data collection techniques using interview methods, and observation. Data collection tools using interview guidelines, observation sheets. In the aspect of Authentification, each health worker account in using the SIMRS application has a different user and password. In the authorization aspect, each health worker can only use the menu features in the SIMRS application according to their respective domains, this is made so that data can be protected from irresponsible people. In the privacy aspect, full access to the SIMRS application can only be done by IT officers and data processing officers, besides that the data security system owned in SIMRS is only a standard system, this can still be done by hacking data by irresponsible parties. The conclusion needs to be re-evaluated regarding the security system used in SIMRS in order to keep electronic medical record data safer from irresponsible parties.